Ultrasonic elasticity determination of 45S5 Bioglass®-based scaffolds: Influence of polymer coating and crosslinking treatment - Li, Wei; Pastrama, Maria-Ioana; Ding, Yaping; Zheng, Kai; Hellmich, Christian; Boccaccini, Aldo R. (Journal of the Mechanical Behavior of Biomedical Materials, 2014)
Highly porous 45S5 Bioglass-based scaffolds with interconnected pore structure are promising candidates for bone tissue engineering due to their bioactivity, biocompatibility, osteogenic and angiogenic effects. In the present study, to ensure the mechanical competence of the 45S5 Bioglass-based scaffolds, their stiffness was adjusted by applying polymer coatings and further crosslinking treatment. A non-destructive ultrasonic technique was used to determine the stiffness of the scaffolds. The stiffness of uncoated scaffolds was shown to increase by applying polymer coatings, and a further increase was achieved by crosslinking the used polymer coatings. All uncoated and polymer-coated scaffolds were confirmed to exhibit stiffness values in the range of reported values in the literature for cancellous bone. A statistical evaluation of combined multiscale ultrasound-nanoindentation measurements indicated that the stiffness of the coated scaffold is directly dependent on the stiffness of the polymer coating.
Keywords: Bioglass®; Elasticity; Polymer coating; Scaffold; Ultrasound